Fake news zealots: Effect of perception of news on online sharing behavior - t'Serstevens, François; Piccillo, Giulia; Grigoriev, Alexander (Frontiers in Psychology, 2022)
Why do we share fake news? Despite a growing body of freely-available knowledge and information fake news have managed to spread more widely and deeply than before. This paper seeks to understand why this is the case. More specifically, using an experimental setting we aim to quantify the effect of veracity and perception on reaction likelihood. To examine the nature of this relationship, we set up an experiment that mimics the mechanics of Twitter, allowing us to observe the user perception, their reaction in the face of shown claims and the factual veracity of those claims. We find that perceived veracity significantly predicts how likely a user is to react, with higher perceived veracity leading to higher reaction rates. Additionally, we confirm that fake news is inherently more likely to be shared than other types of news.Lastly, we identify an activist-type behavior, meaning that belief in fake news is associated to significantly disproportionate spreading (compared to belief in true news).